1991
DOI: 10.1177/106002809102500409
|View full text |Cite
|
Sign up to set email alerts
|

Topical Capsaicin in Dermatologic and Peripheral Pain Disorders

Abstract: Topical capsaicin has been introduced in the U.S. and Canada as a cream indicated for temporary relief of neuralgia following episodes of herpes zoster infections and in the treatment of diabetic neuropathy. Although capsaicin is clinically used as an external analgesic for temporary relief of neuralgia, it has also been widely used as a research tool to study peripheral pain. Capsaicin apparently works to release substance P from sensory nerve fibers and after repeated applications, depletes neurons of substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 28 publications
1
42
0
1
Order By: Relevance
“…The reported indicated that the intake of capsaicin in a typical Indian or Thai diet was about 128 µg/kg human body weight (44). The concentrations of capsaicin in the gastric fluid (1-3 L) would be equivalent to 8-25 µM for an adult human with a body weight of 60 kg.…”
Section: Discussionmentioning
confidence: 99%
“…The reported indicated that the intake of capsaicin in a typical Indian or Thai diet was about 128 µg/kg human body weight (44). The concentrations of capsaicin in the gastric fluid (1-3 L) would be equivalent to 8-25 µM for an adult human with a body weight of 60 kg.…”
Section: Discussionmentioning
confidence: 99%
“…The desensitizing effect of channel activation has been utilized clinically to reduce the afferent transmission of painful stimuli (27). Repeated activation of TRPV1 by chemical stimuli results in calcium-dependent desensitization of the receptor (24).…”
mentioning
confidence: 99%
“…OC for defense formulas can vary in potency fiom 16,000 Scoville Heat Units (S.H.U.) to 1.5 million units, with a 5-10% solution generally recommended as an effective dose (13). However, because OC is inflammatory as well as irritating, increasing the strength also increases the safety risks.…”
Section: Olmrcsin Capsicummentioning
confidence: 99%